116k views
2 votes
What value of m satisfies the equation 6(4m-3)+6=4(4m+11)

User Shawjia
by
4.6k points

2 Answers

6 votes

Answer:

m=7

Explanation:

User Delcon
by
5.0k points
4 votes

Answer:

m=7

Explanation:

6(4m-3)+6=4(4m+11)

use 6 to open the first bracket and use 4 to open the second bracket

24m-18+6=16m+44

solve the first equation

24m-12=16m+44

collect like terms

24m-16m=44+12

then solve

8m=56

divide both sides by 8

m=56/8=7

HOPE THIS HELPS.

User Henrique Barros
by
5.5k points